Pengaruh Pengambilan Keputusan Investasi Dan Kelayakan Investasi Saham Pada Perbankan Syariah Di Bursa Efek Indonesia - Okta Distira, Muhammad Feri; Ilhamy Nasution, Muhammad Lathief; Batubara, Maryam (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of stock investment decision making and stock investment feasibility on the Capital Asset Pricing Model (CAPM) in Islamic banking on the Indonesian Stock Exchange partially and simultaneously. This study uses a quantitative approach. The type of data used is Secondary Data which is obtained from monthly BRIS Stock Price Movement Data on the Indonesia Stock Exchange. There were 43 samples in this study. The analysis techniques used included descriptive statistical analysis, classical assumption test, multiple linear regression test, and hypothesis testing. The results showed that partially the investment decision had a significant positive effect on CAPM with tcount > ttable (2.774>1.684) and a significant value of (0.017<0.05). Partially, investment feasibility has a significant negative effect on CAPM with a tcount > ttable (2.495<1.684) and a significant value of (0.008<0.05). Simultaneously Investment Decision and Investment Feasibility have a significant effect on CAPM. With a significant value of (specify) the value of Fcount > Ftable, namely (3.868> 3.23). While the value of the coefficient of determination is 78%.